A cross-sectional gender-sensitive analysis of depressive symptoms in patients with advanced cancer. (December 2020) - Shapiro, Gilla K; Mah, Kenneth; de Vries, Froukje; Li, Madeline; Zimmermann, Camilla; Hales, Sarah; Rodin, Gary
Background: Patients with advanced cancer commonly report depressive symptoms. Examinations of gender differences in depressive symptoms in patients with advanced cancer have yielded inconsistent findings. Aim: The objective of this study was to investigate whether the severity and correlates of depressive symptoms differ by gender in patients with advanced cancer. Design: Participants completed measures assessing sociodemographic and medical characteristics, disease burden, and psychosocial factors. Depressive symptoms were examined using the Patient Health Questionnaire, and other measures included physical functioning, symptom burden, general anxiety, death related distress, and dimensions of demoralization. A cross-sectional analysis examined the univariate and multivariate relationships between gender and depressive symptoms, while controlling for important covariates in multivariate analyses. Setting/participants: Patients with advanced cancer ( N  = 305, 40% males and 60% females) were recruited for a psychotherapy trial from outpatient oncology clinics at a comprehensive cancer center in Canada. Results: Severity of depressive symptoms was similar for males ( M  = 7.09, SD  = 4.59) and females ( M  = 7.66, SD  = 5.01), t (303) = 1.01, p  = 0.314. Greater general anxiety and number of cancer symptoms were associated with depressive symptoms in both males and females. Feeling like a failure ( β  = 0.192), less death anxiety ( β  = –0.188), severity of cancer symptoms ( β  = 0.166), and older age ( β  = 0.161) were associated with depressive symptoms only in males, while disheartenment ( β  = 0.216) and worse physical functioning ( β  = 0.275), were associated with depressive symptoms only in females. Conclusions: Males and females report similar levels of depressive symptoms but the pathways to depression may differ by gender. These differences suggest the potential for gender-based preventive and therapeutic interventions in this population.